Protocolo de avaliação de risco para desenvolvimento de lesões decorrentes do posicionamento cirúrgico em idosos - Gomes, Silvania Katiussa de Assis (2019)
Introduction: the advancement of technology, through the availability of less invasive and faster surgeries, associated with the technical improvement of professionals, allowed increasing the confidence in surgical procedures, implying a lower rate of postoperative complications and consequent increased surgical elderly population. The surgical positioning of patients is fundamental to provide favorable surgery conditions and to avoid complications due to the permanence in non-physiological positions for prolonged periods. In this context, the creation of a protocol that encompasses perioperative measures becomes an effective strategy for the implementation of the Nursing Care Systematization with instruments that guide the nurse in decision-making, aiming to reduce the risks of injuries resulting from the surgical position. Objective: to propose a risk assessment protocol for lesions due to the positioning in elders submitted to elective surgeries. Method: methodological study to elaborate the protocol and validation of content by specialists, carried out with the participation of 10 judges, six nurses from a University Hospital of a Northeast capital, and four professors and researchers from some Brazilian universities. The Content Validity Index was used to quantify the degree of agreement between the judges. Results: judges’ characterization and the description of the content validation were performed, with a concordance index of 0.95. The judges’ suggestions considered pertinent were followed, which resulted in the technological product: Risk assessment protocol for development of lesions due to surgical positioning in elders (Version 2). Conclusion: the protocol validation was valid to detect/minimize the risks of complications due to surgical positioning, allowing its use as an important strategy to standardize the care and safety of the procedure, representing an advance in the areas of perioperative gerontology and nursing.